Pediatric small intestine cavernous lymphangioma detected via wireless capsule endoscopy: a rare case report - Yang, Xiaoyu; Guan, Junwen; Zhang, Yi (Frontiers in Oncology, 2025)
BackgroundCavernous lymphangioma represents a common lesion of the lymphatic system, yet it is rarely encountered in the small intestine. The diagnosis of small intestinal cavernous lymphangioma poses significant clinical challenges. This case report presents the optimal diagnostic and therapeutic management of pediatric small intestinal cavernous lymphangioma.Case descriptionA 27-month-old male presented with recurrent syncopal episodes, hematochezia, and anemia. Small intestinal abnormalities were detected via wireless capsule endoscopy. Single-port laparoscopic surgery was subsequently performed, intraoperatively revealing a 3×3×6 cm ileal lesion located 95 cm proximal to the ileocecal valve. Segmental bowel resection was completed, with postoperative histopathological confirmation of cavernous lymphangioma.ConclusionPediatric cavernous lymphangioma of the small intestine is an exceedingly rare clinical disease with a multifaceted diagnostic process. Wireless capsule endoscopy is strongly recommended as a pivotal diagnostic modality for small intestine cavernous lymphangioma. Upon confirmation of the intestine lesion, immediate single-port laparoscopic resection should be implemented as the therapeutic imperative.